2002
DOI: 10.2519/jospt.2002.32.7.336
|View full text |Cite
|
Sign up to set email alerts
|

Reliability by Surgical Status of Self-Reported Outcomes in Patients Who Have Shoulder Pathologies

Abstract: Study Design: A test-retest design was used to evaluate the reliability of the self-report sections of 4 shoulder pain and disability scales. Objective: The objective of the study was to compare interitem consistency and test-retest reliability by surgical status (postoperative versus nonoperative) and to evaluate the effect of surgical status in the prediction of retest scores. Background: Patients and healthcare providers evaluate shoulder status based on self-evaluations of pain and disability. Shoulder out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…Testretest reliability of the pain scale and error estimates of the CSS total score have been reported. 10,13 The patient can complete the self-report section of the CSS in approximately 5 minutes and the clinician can complete the range of motion and strength portion in approximately 10 minutes. This scale has been used internationally for reporting outcome of various shoulder conditions.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Testretest reliability of the pain scale and error estimates of the CSS total score have been reported. 10,13 The patient can complete the self-report section of the CSS in approximately 5 minutes and the clinician can complete the range of motion and strength portion in approximately 10 minutes. This scale has been used internationally for reporting outcome of various shoulder conditions.…”
Section: Instrumentationmentioning
confidence: 99%
“…17 This scale contains 1 item that dichotomizes the patient's response into ''satisfied and better'' and ''not satisfied and worse.'' 13,17 Limiting patient responses to these 2 options allows for only a gross estimate of the patient's level of satisfaction. 13 Cook and colleagues 13 reported an ICC value of 0.79 for this item in patients post shoulder surgery.…”
Section: 44mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Cook et al 3 investigated the reliability of 4 selfreports of shoulder function and suggested that the University of California at Los Angeles (UCLA) Shoulder Scale is inappropriate for use in individuals who did not have surgery because of low reliability. 3 Additionally, self-report measures may also be subject to perceptual differences because function is influenced by psychological, social, environmental, and physical factors. 6,19 Accordingly, a battery of function-related tests has the potential to complement functional outcome assessment in patients with various shoulder pathologies.…”
mentioning
confidence: 99%
“…Functional status was assessed using University of California Los Angeles (UCLA) shoulder end result assessment [14], simple shoulder test (SST) [15] and American Shoulder and Elbow Society (ASES) shoulder index [16].…”
Section: Methodsmentioning
confidence: 99%